PENDAMPINGAN PEMBUATAN LABEL PADA PRODUK KEMASAN UMKM DI DESA BESUK, KECAMATAN BANTARAN, KABUPATEN PROBOLINGGO - Taufikurrahman, Taufikurrahman; Baihaqi Yusuf, Ahmad Riki; Fatimatuzzahro, Ucik; Febriari Rahmawati, Ernesta; Fadila Aprilia, Farah; Nur Fadillah, Ayu; Setiawati, Putri; Tri Aidhaningtyas, Fera; Rahma Krisna, Nabilah; Surya Murti, Deva; Laksmana Putra, Setyo Febri; Ardiyana, I Gede (CV. Era Digital Nusantara, 2022)
Marketing strategy holds a very important control in the success of product acceptance in the community, but many Small and Medium Enterprise (SME) ignore this. Labels and packaging are one of the keys for Small and Medium Enterprise (SME) to further increase the selling value of their products. Empowerment activities to improve the quality of Small and Medium Enterprise (SME) are carried out through assistance in making labels on packaged products. The object of this activity is Small and Medium Enterprise (SME) actors in Besuk Village, Bantaran District, and Probolinggo Regency. One of the Small and Medium Enterprise (SME) products in this village is banana chips, cassava chips, elephant ears, and lard. The problem with these Small and Medium Enterprise (SME) is the low quality of label and packaging designs for their products, as well as the lack of supporting facilities and infrastructure for designing product packaging labels. So that the products of Small and Medium Enterprise (SME) partners are less attractive than similar competitor products. The Small and Medium Enterprise (SME) products in Besuk Village it self also do not have a broad market share, so they are constrained in increasing the number of products that will be produced. Implementation methods used include: 1) pre-activity; 2) core activities; 3) activity evaluation. Where the problem solving of the Small and Medium Enterprise (SME) constraints above is in the form of assisting in making labels on packaged products so that they can meet the existing label requirements and also look more attractive. The results of the activity are in the form of training on the manufacture of product packaging labels as well as the manufacture of ready to use designs for these Small and Medium Enterprise (SME).